Genetic polymorphisms of MASP2, TG5, and DQA1 genes in Holstein and Brown Swiss dairy cows - El Zeer, A; Fouda, M; Darwish, R; Ateya, A (Journal of the Hellenic Veterinary Medical Society, 2023)
The objective of this study was to investigate polymorphisms of MASP2, TG5 and DQA1 genes using PCR-DNA sequencing in seventy Holstein, and Brown Swiss dairy cows (35 cows each). Under complete aseptic condition, blood samples were collected from each animal into tubes containing disodium EDTA as an anticoagulant for DNA extraction. PCR was carried out for amplification of 305-bp of MASP2, 545-bp of TG5, and 373-bp of DQA1 genes. DNA sequencing assessment elaborated nucleotide sequence variations in forms of single nucleotide polymorphisms (SNPs) between two breeds. The SNPs identified in the investigated genes for Holstein breed were A46G in MASP2 gene and C371T in TG5 gene. A characteristic T53C SNP was also reported for Brown Swiss breed in DQA1 gene. Chi-square revealed a significant variation in distribution of all identified SNPs (P < 0.001). Consequently, identified SNPs could be used as candidates and a reference guide for efficient characterization of Holsteins, and Brown Swiss breeds; therefore, developing a marker assisted selection (MAS) for production and immunity traits in breeds of dairy cattle.